A new lignicolous hyphomycete species of Neospadicoides in Xenospadicoidaceae (Xenospadicoidales) from Thailand - Xu, Rong-Ju; Zhu, Ying-An; Li, Lu; Yu, Feng-Ming; Boonmee, Saranyaphat; Zhao, Qi (Phytotaxa, 2023)
Neospadicoides amphibia sp. nov. (Xenospadicoidaceae, Xenospadicoidales) was found on dead and submerged decaying woods in freshwater and terrestrial habitats in Chiang Mai and Chiang Rai Provinces, Thailand. This new species is characterized by asexual hyphomycete, hairy effuse, dark colonies, erect, straight to flexuous, dark brown conidiophores, with polytretic, integrated terminal and intercalary conidiogenous cells and obovoid, 3-euseptate, pigmented conidia. The multi-gene phylogeny of the combined ITS, LSU, SSU, and RPB2 sequence data placed these two isolates within Neospadicoides as a distinct sister lineage to species N. thailandica with highly support. Therefore, the new species, Neospadicoides amphibia, was described and illustrated based on morphological and phylogenetic evidence.